Desenvolvimento e validação de metodologia bioanalítica e sua aplicação para a determinação da farmacocinética e biodistribuição do paclitaxel e genisteína co-encapsulados em nanopartículas multicompartimentais - Veloso, Danillo Fabrini Maciel Costa (2014)
Ultra-sensitive and specific bioanalytical methods are needed to quantify drugs used in cancer treatment and monitor its absorption, distribution and elimination in body fluids and tissues. Most anticancer drugs are relatively unstable substances, subject to an intensive metabolism in vivo and degradation during pretreatment of the sample. Thus, due to high specificity, sensitivity and not mandatory derivatization, high efficiency liquid chromatography coupled to mass spectrometry has emerged as one of the techniques for in vivo monitoring of drugs for appropriate cancer treatment. This study investigated the pharmacokinetics and biodistribution of paclitaxel and genistein after intraperitoneal administration in mice, in a formulation where paclitaxel was encapsulated in polymeric nanoparticles, coated with a lipid bilayer containing genistein. A bioanalytical method was developed and validated according to the Food and Drugs Administration and RDC 027/2012 ANVISA. To prepare the samples was used one liquid-liquid extraction, which was quantified by liquid chromatography coupled to a mass spectrometer, determining the levels of paclitaxel and genistein in different biological matrices. The results of bioanalytical method validation show that using weighted (1/x2 ), the calibration curve was linear over the concentration range examined (5-2000 ng/ml for paclitaxel and 10-5000 ng/mL for genistein) with R2 > 0.98 in all the calibration curves for both analytes. The precision and inter and intra-day accuracies were evaluated in three analytical runs, analyzed on different days with triplicate samples of quality control, low, medium, high and lower limit of quantification concentrations, and had no greater variation than acceptable (15 %) showing results ranging from 85.90 to 113.80 % and 96.10 to 99.80 % recoveries for both analytes and internal standard (ketoconazole). Paclitaxel, genistein and internal standard were stable at all storage tests, both in solution and in the biological matrix (short term stability, post-processing stability) and cycles of freezing and thawing. The validated method was used to calculate the main pharmacokinetic parameters of paclitaxel and genistein in plasma after administration by intraperitoneal route: t1/2 = 2,86 e 0,89 h; tmax = 8,00 e 0,11 h; Cmax = 2,54 e 3,73 µg/mL, AUC0-14 = 19,61 e 1,96 µg *h/mL; AUC0-∞ = 21,54 e 2,01 µg*h/mL and clearance. The pharmacokinetics data indicate that this nanocarrier system features for controlled drugs release maintaining their concentrations sustained in the bloodstream, thus remaining longer at the site of administration and modular managing their biodistribution in a different way in a healthy animal and a tumor bearing animals.